2022
DOI: 10.3389/fmars.2021.796488
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Population Collapse of a Key Marine Predator in the Northern Antarctic Peninsula Endangers Genetic Diversity and Resilience to Climate Change

Abstract: Antarctic fur seals (AFS) are an ecologically important predator and a focal indicator species for ecosystem-based Antarctic fisheries management. This species suffered intensive anthropogenic exploitation until the early 1900s, but recolonized most of its former distribution, including the southern-most colony at Cape Shirreff, South Shetland Islands (SSI). The IUCN describes a single, global AFS population of least concern; however, extensive genetic analyses clearly identify four distinct breeding stocks, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 136 publications
(234 reference statements)
0
30
0
Order By: Relevance
“…Recent detailed genetic studies support the two regional populations being distinct (Paijmans et al 2021). Although the South Shetland Islands population appeared to have stabilised at a level of about one eighth of its pre-exploitation level by the early twenty-first century (Hucke- Gaete et al 2004;Hoffman et al 2018), it has subsequently shown a further substantial decrease in numbers suggested to be a consequence of a sustained increase in top-down predation of pups by leopard seals (Krause et al 2022). However, a study of seal hair abundance in a core of accumulated terrestrial sediment on a coastal raised beach on King George Island (Sun et al 2004) inferred large levels of variation in the size of the local fur seal population over the last 1500 years.…”
Section: The Specific Case Of Antarctic Fur Seal Population Recoverymentioning
confidence: 99%
See 4 more Smart Citations
“…Recent detailed genetic studies support the two regional populations being distinct (Paijmans et al 2021). Although the South Shetland Islands population appeared to have stabilised at a level of about one eighth of its pre-exploitation level by the early twenty-first century (Hucke- Gaete et al 2004;Hoffman et al 2018), it has subsequently shown a further substantial decrease in numbers suggested to be a consequence of a sustained increase in top-down predation of pups by leopard seals (Krause et al 2022). However, a study of seal hair abundance in a core of accumulated terrestrial sediment on a coastal raised beach on King George Island (Sun et al 2004) inferred large levels of variation in the size of the local fur seal population over the last 1500 years.…”
Section: The Specific Case Of Antarctic Fur Seal Population Recoverymentioning
confidence: 99%
“…Large populations of fur seals on the sub-and other peri-Antarctic islands, but particularly on South Georgia and the South Shetland Islands (Fig. 4), were the first to suffer uncontrolled overexploitation, almost being driven to extinction (Bonner 1968;Forcada and Staniland 2009;Paijmans et al 2021;Krause et al 2022). The sequence of rampant overexploitation was followed by the great whales, with the development of, initially, shore-based whaling stations on several peri-Antarctic islands in the early twentieth century, and later of the pelagic whaling industry (e.g.…”
Section: Southern Ocean Marine Resource Exploitationmentioning
confidence: 99%
See 3 more Smart Citations